Analisis Yuridis Terhadap Tindak Pidana Usaha Perikanan Yang Tidak Memiliki Perizinan Berusaha Di Indonesia (Studi Kasus Putusan Pengadilan Negeri Bitung Nomor 5/Pid.Sus-Prk/2025/Pn Bit) - Yulaekhah, Umi; Huda, Misbahul (FOCUS, 2026)
The fisheries sector plays a strategic role in supporting economic growth, food security, and Indonesia’s maritime sovereignty. However, illegal fishing remains a serious issue that causes state losses and marine ecosystem degradation. This problem is closely related to violations of fisheries business licensing requirements, which function as key instruments for controlling sustainable resource management. This study examines legal accountability for fisheries business actors operating without valid licenses and analyzes judicial considerations in Case Number 5/Pid.Sus-PRK/2025/PN Bit. The findings show that the enforcement of criminal and administrative sanctions reflects efforts to balance justice, legal certainty, and environmental sustainability. Under the Fisheries Law, intentional licensing violations may result in imprisonment and fines, alongside administrative sanctions under the Job Creation Law. In the case of Crisanto Sumilhig Langamon, the court imposed imprisonment, a monetary fine, and confiscation of fishing equipment, emphasizing both punitive and preventive functions of sanctions. This decision demonstrates the application of the combined theory (verenigings theorie), prioritizing justice, legal certainty, and legal utility in fisheries law enforcement.